2016
DOI: 10.1537/ase.151206
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of craniofacial measurements between Ryukyuan and mainland Japanese females using lateral cephalometric images

Abstract: Using lateral cephalometric images, we compared the skeletal and soft tissue configurations of Ryukyuan and mainland Japanese females. We collected lateral cephalometric images of 30 females each from Okinawa Island and mainland Japan. Sixty landmarks were plotted on each image. Then, based on the coordinates of the landmarks, 68 distances and 34 angles were calculated according to orthodontic and anthropometric methods. We confirmed that the Ryukyuans have a smaller height in the upper and midfacial region th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In another study, an analysis of data from mainland Japan and the Ryukyu Islands found that women from the island of Japan had smaller mandibular incisor, less depth of the upper lip, and an inclined to the front mandibular symphysis [26].…”
Section: Introductionmentioning
confidence: 96%
“…In another study, an analysis of data from mainland Japan and the Ryukyu Islands found that women from the island of Japan had smaller mandibular incisor, less depth of the upper lip, and an inclined to the front mandibular symphysis [26].…”
Section: Introductionmentioning
confidence: 96%
“…Using CT images, the present study aimed to reveal the anatomical backgrounds of the upper facial variations, particularly focusing on the nasal root protrusion and the eyeball position. In this context, Ryukyu Islanders and mainland Japanese are appropriate subjects, because there are significant variations in facial morphologies (Fukase et al, 2012;Miyazato et al, 2014;Yamauchi et al, 2016). For example, the people originating from Okinawa Island (one of the Ryukyu Islands in Japan) have a more chiseled face than those originating from mainland Japan (Miyazato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%